RETRACTED: How Organizations Create Employee Based Brand Equity: Mediating Effects of Employee Empowerment - Li, Zhengmin (Frontiers in Psychology, 2022)
In the present era organizations are trying to get success in the market by creating a competitive advantage, however, it has been argued in the literature that the fashion of creating competitive advantage through tangible resources is now gaining unpopularity among organizations and there is a shift towards human capital for organizational competitiveness. This study has made an attempt towards this focus and investigated the phenomenon of employee brand based equity. For this purpose data has been collected from manufacturing sector through personally administrated questionnaires. Total 400 questionnaires were floated. After discarding the partially filled questionnaires, 325 were left which were later analyzed on the bases of structural equation modeling (SEM) approach by assessing the measurement model and structural model. The outcome of the study revealed that psychological attachment, internal communication and employee organization fit brings positive change in employee attitudes and it promotes employee brand based equity. Similarly, it has also been proved that employee empowerment also plays a mediating role.